CRM and Mobile Technology - Salhotra, Karan (My University, 2008)
Thesis includes the research work on CRM and Mobile multimedia i.e. what is CRM and how it is becoming a driving force nowadays for improvement in technology
M.E. Thesis(Computer Science)
Keywords: CRM; Vectored Interrupt Controller